Classic Car Collector: Passion Investment: Study On Classic Car Collectors in Semarang - Bidadari Yuritza Destilasilika; Mirwan Surya Perdhana (PT. Publikasiku Academic Solution, 2023)
This research is a qualitative research. Data collection was carried out using the interview method. This study aims to find out facts about passion investment in classic car collectors in Semarang. In recent years, the investment trend in Indonesia has increased. One alternative investment that is in demand is investing in art. Items that have works of art such as antiques can be used as an investment. In 2023 the number of investors investing in classic cars has increased from the previous year. In addition, over the past decade investing in classic cars has financially done better than many other collectibles such as stamps or coins. In this study generate data regarding the facts of investing in classic cars. Potential investors need significant knowledge about classic cars because not all old cars can be considered classics. The car is rare or available everywhere. Classic cars are depreciable assets, so it is very important for investors to know how to maintain the value of classic cars. Investing in classic cars is a little risky because to generate a reasonable return, investors must buy the vehicle and repair or maintain it before reselling it. Most classic car investors view their investments as a hobby rather than a method of making material gains.